Time to rethink export controls for strengthened US-EU cooperation and global trade rules - Matthias Bauer; Dyuti Pandya (European Centre for International Political Economy (ECIPE), 2024)
The escalation of broad export controls by the US, under the guise of national security and the aim to curb technological transfers to potential adversaries,1 marks a new epoch of bureaucratic oversight. The US push for broad export controls also underscores a critical juncture in US-EU relations and global trade rules. Broad export restrictions not only challenge the very foundation of free trade but also contribute to the erosion of Western technology leadership.2 Unilateral export controls may start strong but eventually lose effectiveness and become counterproductive,3 pushing non-US companies, particularly in the semiconductor sector, to find alternatives to US components.
Keywords: 330